2002
DOI: 10.1074/jbc.m208023200
|View full text |Cite
|
Sign up to set email alerts
|

The Components of the Saccharomyces cerevisiaeMannosyltransferase Complex M-Pol I Have Distinct Functions in Mannan Synthesis

Abstract: The yeast Saccharomyces cerevisiae processes N-linked glycans in the Golgi apparatus in two different ways. Whereas most of the proteins of internal membranes receive a simple core-type structure, a long branched polymer termed mannan is attached to the glycans of many of the proteins destined for the cell wall. The first step in mannan synthesis is the initiation and extension of an ␣-1,6-linked polymannose backbone. This requires the sequential action of two enzyme complexes, mannan polymerases (M-Pol) I and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 64 publications
5
51
0
Order By: Relevance
“…3 Thus, the clustering of O-linked sugars requires high efficiency sugar transfer, which might be provided by mannosyltransferase complexes. That oligomerization enhances enzyme function has been proven for other glycosyltransferases such as UDPGlcNAc:dolichol-P GlcNAc-1-P transferase (50) or the mannosyltransferase complexes M-Pol I and M-Pol II (51)(52)(53). Furthermore, even though members of the PMT1 and PMT2 subfamily act on the same protein substrate (14,25), they might actually O-mannosylate different serine and threonine residues within one and the same protein.…”
Section: Heteromeric Protein Complexes Between Pmt1 and Pmt2 Subfamilmentioning
confidence: 99%
“…3 Thus, the clustering of O-linked sugars requires high efficiency sugar transfer, which might be provided by mannosyltransferase complexes. That oligomerization enhances enzyme function has been proven for other glycosyltransferases such as UDPGlcNAc:dolichol-P GlcNAc-1-P transferase (50) or the mannosyltransferase complexes M-Pol I and M-Pol II (51)(52)(53). Furthermore, even though members of the PMT1 and PMT2 subfamily act on the same protein substrate (14,25), they might actually O-mannosylate different serine and threonine residues within one and the same protein.…”
Section: Heteromeric Protein Complexes Between Pmt1 and Pmt2 Subfamilmentioning
confidence: 99%
“…In it, M--Pol I, a heterodimer, acts first to extend the Och1--derived Man with further α1,6--linked mannoses. Analyses of mutants in the DXD motifs of Mnn9 and Van1 indicated that Mnn9 likely adds the first α1,6--liked Man, which is extended with 10--15 α1,6 mannoses in Van1--requiring reactions (Stolz and Munro, 2002;Rodionov et al 2009). This α1,6 backbone is then elongated with 40--60 α1,6 Man by M--Pol II.…”
Section: Formation Of Core Type N--glycan and Mannan Outer Chainsmentioning
confidence: 99%
“…The protein(s) involved have not been identified, but presumably either they, or M-Pol I, can tell from the context of an N-glycan which type of structure it is to bear (Lewis and Ballou 1991;Stolz and Munro 2002;Rodionov et al 2009). Core-type structures are completed when that a1,2-Man, as well as the two other terminal a1,2-Man on the Man 8 GlcNAc 2 structure, receives a1,3 mannoses from Mnn1.…”
Section: N-glycosylationmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting model to explain the biosynthesis of either extended or core-type oligosaccharides has been recently proposed (7). In this model, the protein carrying N-glycan chains with the first ␣-1,6-mannose added by Och1p interacts with Mnn9p and depending on the nature of this interaction Mnn9 would add either an ␣-1,6-or ␣-1,2-mannose.…”
Section: Discussionmentioning
confidence: 99%